Heterogeneity of Group 2 Innate Lymphoid Cells Defines Their Pleiotropic Roles in Cancer, Obesity, and Cardiovascular Diseases - Ikutani, Masashi; Nakae, Susumu (Frontiers in Immunology, 2022)
Group 2 innate lymphoid cells (ILC2s) are typically known for their ability to respond rapidly to parasitic infections and play a pivotal role in the development of certain allergic disorders. ILC2s produce cytokines such as Interleukin (IL)-5 and IL-13 similar to the type 2 T helper (Th2) cells. Recent findings have highlighted that ILC2s, together with IL-33 and eosinophils, participate in a considerably broad range of physiological roles such as anti-tumor immunity, metabolic regulation, and vascular disorders. Therefore, the focus of the ILC2 study has been extended from conventional Th2 responses to these unexplored areas of research. However, disease outcomes accompanied by ILC2 activities are paradoxical mostly in tumor immunity requiring further investigations. Although various environmental factors that direct the development, activation, and localization of ILC2s have been studied, IL-33/ILC2/eosinophil axis is presumably central in a multitude of inflammatory conditions and has guided the research in ILC2 biology. With a particular focus on this axis, we discuss ILC2s across different diseases.